Long-term Patiromer Use and Outcomes Among US Veterans With Hyperkalemia and CKD: A Propensity-Matched Cohort Study - Yoshitsugu Obi; Fridtjof Thomas; Ankur A. Dashputre; Patricia Goedecke; Csaba P. Kovesdy (Kidney Medicine, 2024)
Rationale & Objective: Patiromer is a potassium binder approved for the long-term management of hyperkalemia. Although patiromer use among patients with advanced chronic kidney disease (CKD) has been shown to reduce the discontinuation of renin-angiotensin-aldosterone system inhibition therapy, it remains unclear whether patiromer can improve clinical outcomes. The aim of this study was to examine the association of long-term patiromer use with clinical outcomes among hyperkalemic patients with CKD. Study Design: This was a longitudinal observational study. Setting & Participants: We evaluated a national cohort of 854,217 US Veterans who had at least 1 serum potassium measurement of ≥5.1 mEq/L and were treated at US Department of Veterans Affairs health care facilities between January 2016 and September 2019. Exposure: The exposure was long-term patiromer use. Outcomes: The outcomes were as follows: (1) composite endpoint of kidney failure with replacement therapy (KFRT) or all-cause death and (2) all-cause death including the post-KFRT period. Analytical Approach: Cox proportional Fine-Gray subdistribution hazard models were used in a propensity-matched cohort. Results: Among 2,004 patients who ever used patiromer during the study period (0.2% of the cohort), 666 met the criteria for long-term patiromer use. We matched 308 long-term patiromer users to 308 nonusers based on propensity scores. The median estimated glomerular filtration rate was 23.5 mL/min/1.73m2, and the median potassium level was 5.2 mEq/L. Approximately 45% were on renin-angiotensin system inhibitor(s) at baseline. During follow-up, 93 patients developed KFRT, and 134 patients died. Long-term patiromer users, when compared to nonusers, experienced a 26% lower risk of the composite outcome (HR, 0.74; 95% CI, 0.53-1.01; P = 0.06) and a 41% lower risk of all-cause mortality (HR, 0.59; 95% CI, 0.41-0.84; P = 0.003). Limitations: The study cohort included mostly male veterans with relatively short follow-up periods. Conclusions: Long-term patiromer use was associated with a lower risk of all-cause mortality among patients with CKD and hyperkalemia. Long-term potassium binder use for hyperkalemia may improve clinical outcomes in CKD. Plain-Language Summary: Hyperkalemia is a common complication of chronic kidney disease (CKD) and can result in the discontinuation of renin-angiotensin-aldosterone system inhibition therapy, a cornerstone of CKD management. Patiromer is a new potassium binder approved for the long-term management of hyperkalemia, but it remains unclear whether patiromer can improve clinical outcomes. We examined a cohort of US Veterans with hyperkalemia between January 2016 and September 2019 and found that patiromer use was uncommon for treating hyperkalemia during this study period. We then matched 308 long-term patiromer users and 308 nonusers based on propensity scores. Long-term patiromer users, when compared to nonusers, experienced a 26% lower risk of the composite outcome and a 41% lower risk of all-cause mortality. These findings indicate that long-term potassium binder use for hyperkalemia may improve clinical outcomes in CKD.